Efficacy of Platelet Rich Plasma in Treatment of knee Osteoarthritis: General Survey of Cases at Tertiary Center in Kathmandu, Nepal - Shah, Manish Bikram; Jha, Anik; Nepal, Prabin; Dabadi, Sambardhan (Annapurna Journal of Health Sciences, 2023)
Introduction: Knee osteoarthritis (OA) is a common degenerative disease of knee caused by disruption of cartilage and joint inflammation. Mostly affecting the people above the age of 60, OA is one of the topmost disease causing disability in elderly population. The prevalence of OA in Nepal is also high. Traditional treatment protocols including analgesics, steroid, and physiotherapy are refractory after certain level and knee replacement is highly expensive in Nepal. Platelet Rich Plasma (PRP) therapy has emerged as one of the convincing treatment method for OA. Methods: This prospective cross sectional study was conducted at Annapurna Neurological Institute and Allied Sciences, Kathmandu, Nepal which included total of 203 patients with knee OA, they were treated with PRP injection and the results were evaluated using Ms excel and SPSS. Results: The results demonstrated, the pain subsided by 57.72% after administration of 3rd dose of PRP. The WOMAC scoring before PRP was 80 (mean value), which reduced to 72, 52 and 34 after the first, second and third dose respectively. Conclusion: Platelet-Rich Plasma (PRP) therapy has shown promising results as a potential treatment option for knee osteoarthritis. The results proved PRP as an effective, minimally invasive, and relatively cheaper treatment option for patients with knee OA.